Niobium Boride Layers Deposition on The Surface AISI D2 Steel by a Duplex Treatment - PAZARLIOĞLU, SÜLEYMAN SERDAR (AMER INST PHYSICS, 2015)
In this paper, we investigated the possibility of deposition of niobium boride layers on the surface of AISI D2 steel by a duplex treatment. At the first step of duplex treatment, boronizing was performed on AISI D2 steel samples at 1000 degrees C for 2h and then pre-boronized samples niobized at 850 degrees C, 900 degrees C and 950 degrees C using thermo-reactive deposition method for 1-4 h. The presence of the niobium boride layers such as NbB, NbB2 and Nb3B4 and also iron boride phases such as FeB, Fe2B were examined by X-ray diffraction analysis. Scanning electron microscope (SEM) and micro-hardness measurements were realized. Experimental studies showed that the depth of the coating layers increased with increasing temperature and times and also ranged from 0.42 mu m to 2.43 mu m, depending on treatment time and temperature. The hardness of the niobium boride layer was 2620 +/- 180 HV0.005.
Keywords: Niobium boride; AISI D2; Duplex treatment